PENERAPAN STRATEGI PEMBELAJARAN PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 014 GERINGGING BARU - Syakban Syakban (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research was conducted at the Public Elementary School 014 Geringging Baru. The subjects of this study were 21st grade V students consisting of 10 male students and 11 female students. This research was conducted because of the low learning outcomes of science students. the strategy used in this research is concept map learning. The purpose of this study was to improve the learning outcomes of science students in grade V SD Negeri 014 Geringging Baru. In this study using classroom action research (CAR) which consists of two cycles, each cycle consisting of 1) planning, 3) implementation, 4) observation, and 5) reflection. The results showed, in the basic score, 10 students completed as many as 47.6% while 11 students who did not complete were as many as 52.1%. In the first cycle, students who completed as many as 15 people with a percentage of 71.4%, while students who did not complete as many as 6 people with a percentage of 28.6%. In cycle II, 20 students completed 95.2%, while those who did not complete 1 were 4.7%. From these results, the researcher can conclude that the application of the concept map learning strategy can improve the learning outcomes of science students in grade V SD Negeri 014 Geringging Baru